To Purge or Not to Purge? An Individual-Level Quantitative Analysis of Elite Purges in Dictatorships. Issue 2 (16th April 2023) - Goldring, Edward; Matthews, Austin S.
Abstract: Why do dictators purge specific elites but not others? And why do dictators purge these elites in certain ways? Examining these related questions helps us understand not only how dictators retain sufficient competence in their regimes to alleviate popular and foreign threats, but also how dictators nullify elite threats. Dictators are more likely to purge first-generation elites, who are more powerful because they can negotiate their role from a position of strength and possess valuable vertical and horizontal linkages with other elites. Further, dictators tend to imprison purged first-generation elites – rather than execute, exile or simply remove them – to avoid retaliation from other elites or the purged elite continuing to sow discord. We find empirical support for our predictions from novel data on autocratic elites in 16 regimes from 1922 to 2020.